FORMATIVE PERIOD IN THE NORTHERN ANDES AND ITS RELATIONS WITH CENTRAL ANDES - Mesía Montenegro, Christian (2014)
This paper reviews the Ecuadorian Formative (4500-300 ANE) in relationship with its counterpart in the Central Andes (1800-300 ANE), trying to establish the mechanisms that operated processes of cultural transmission and their outcomes, which reflects in the archaeological record (basically ceramics) the level of interaction between these two areas, especially during the height of Chorrera, Cupisnique and Chavín societies.